2021
DOI: 10.1021/acs.jcim.0c01457
|View full text |Cite
|
Sign up to set email alerts
|

Targeting SARS-CoV-2 M3CLpro by HCV NS3/4a Inhibitors: In Silico Modeling and In Vitro Screening

Abstract: Currently the entire human population is in the midst of a global pandemic caused by SARS-CoV-2 ( S evere A cute R espiratory S yndrome Co rona V irus 2). This highly pathogenic virus has to date caused >71 million infections and >1.6 million deaths in >180 countries. Several vaccines and drugs are being studied as possible treatments or prophylactics of this viral infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 46 publications
1
34
0
Order By: Relevance
“…Boceprevir and telaprevir are approved protease inhibitors for treating hepatitis caused by the hepatitis C virus. Both compounds have been identified several times as covalent inhibitors of the SARS-CoV-2 M-pro [ 43 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. New bicycloproline derivatives have been designed and synthesized from them both [ 59 ].…”
Section: Sars-cov-2 M-pro Inhibitorsmentioning
confidence: 99%
“…Boceprevir and telaprevir are approved protease inhibitors for treating hepatitis caused by the hepatitis C virus. Both compounds have been identified several times as covalent inhibitors of the SARS-CoV-2 M-pro [ 43 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. New bicycloproline derivatives have been designed and synthesized from them both [ 59 ].…”
Section: Sars-cov-2 M-pro Inhibitorsmentioning
confidence: 99%
“…Interestingly, many protease inhibitors were clinically used for HIV treatments [43], of which Lopinavir, Indinavir, and Darunavir have been repurposed to inhibit SARS-CoV-2 M pro [44]. The HCV NS3-4A protease drug, boceprevir, could inhibit SARS-CoV-2 replication by targeting M pro in our and other groups' independent studies [45,46]. To be noted, PRRSV belongs to Arteriviridae.…”
Section: Discussionmentioning
confidence: 64%
“…To date, there is no drug specifically formulated for the treatment of Covid-19 and approved by the FDA. Therefore, specific candidates were repurposed from their actual use among the best results, such as the antiretrovirals boceprevir, asunaprevir, narlaprevir, paritaprevir, and telaprevir, used for the hepatitis C and Lopinavir for HIV treatments, whose effect on the protein Mpro are still being evaluated [72,73]. In our study, when we compared the inhibitory effect of Lopinavir to Rutin, we observed a similar positive effect between both compounds within the Mpro pocket, confirming the potential of Rutin against SARS-CoV-2 Mpro.…”
Section: Discussionmentioning
confidence: 99%